Temanummerets forord - Andersen, Peter B.; Jacobsen, Brian Arly; Kühle, Lene; Christensen, Henrik Reintoft; Pedersen, Heidi Frølund; Würtzen, Hanne; la Cour, Peter; Sørensen, Jesper F. (Religionsvidenskabeligt Tidsskrift, 2021)
Forord til temanummeret om COVID-19, religion og trivsel i Danmark.